Synergistic effects of herbicide and nano-fertilizer integration on weed control, wheat productivity, and economics - Patidar, Durgesh Kumar; Choudhary, Vijay Kumar; Dr. J. S. Mishra (The Indian Journal of Agricultural Sciences, 2026)
Weeds pose a major constraint to wheat production, and herbicides remain one of the most effective and economical tools for their management. Meanwhile, the use of nano-fertilizers is gaining traction due to their efficiency, with top dressing often coinciding with post-emergence herbicide applications. This overlap raises the question of compatibility between herbicides and nano-fertilizers and their combined impact on weed control and crop performance. To address this, the present study evaluated the compatibility of three post-emergence herbicides at field doses with nano-fertilizers (nano-urea and nano-DAP, both individually and in combination). Results revealed that clodinafop + metsulfuron (60 + 4 g ai/ha) combined with nano-urea (4 mL/L) proved most effective, recording the lowest weed density (9.4 no./m²), weed biomass (9.46 g/m²), and the highest weed control efficiency (94.15%). It also showed the lowest weed index and NDVI (0.377) between the rows, whereas the unweeded control had the highest NDVI (0.704), reflecting greater weed pressure. This treatment also significantly improved growth parameters including plant height, tillers/m², dry matter accumulation, leaf area index, crop growth rate, relative growth rate and net assimilation rate as well as yield attributes such as effective tillers, spike length and weight, grains per spike, and test weight. The highest grain yield (4910 kg/ha) and straw yield (6088 kg/ha) were achieved with clodinafop + metsulfuron plus nano-urea, though yields were statistically comparable to other combinations involving metsulfuron and mesosulfuron + iodosulfuron with nano-urea. The same treatment also recorded the highest net returns (₹89,943/ha) and B: C (3.32). Notably, the sole application of mesosulfuron + iodosulfuron (12 + 2.4 g/ha) caused phytotoxicity up to level 3, but this effect was mitigated when used in combination with nano-urea, enabling faster crop recovery.